Lineage-Specific Expansion of Plasmodium falciparum Parasites With pfhrp2 Deletion in the Greater Mekong Subregion - Gibbons, Justin (J Infect Dis, 2020)
Deletion of the pfhrp2 gene in Plasmodium falciparum can lead to false-negative rapid diagnostic test (RDT) results, constituting a major challenge for evidence-based malaria treatment. Here we analyzed the whole genome sequences of 138 P. falciparum clinical samples collected from the China-Myanmar boarder for pfhrp2 and pfhrp3 gene deletions. We found pfhrp2 and pfhrp3 deletions in 9.4% and 3.6% of samples, respectively, with no samples harboring deletions of both genes. The pfhrp2 deletions showed 2 distinct breakpoints, representing 2 different chromosomal deletion events. A phylogenetic analysis performed using genome-wide single-nucleotide polymorphisms revealed that the 2 pfhrp2 breakpoint groups as well as all the pfhrp3-negative parasites formed separate clades, suggesting they might have resulted from clonal expansion of pfhrp2- and pfhrp3-negative parasites. These findings highlight the need for urgent surveys to determine the prevalence of pfhrp2-negative parasites causing false-negative RDT results and a plan for switching of RDTs pending the survey results.